Antibody persistence after serogroup C meningococcal conjugate immunization of United Kingdom primary-school children in 1999-2000 and response to a booster: a phase 4 clinical trial - Perrett, K; Winter, A; Kibwana, E; Jin, C; John, T; Yu, L; Borrow, R; Curtis, N; Pollard, A (University of Chicago Press, 2010)
Background: After immunization with serogroup C meningococcal (MenC) conjugate vaccine, antibody responses and vaccine effectiveness are sustained in adolescents, in contrast to rapid waning in young children. We investigated the persistence of serum bactericidal antibody (SBA) titers in children 6 years after immunization with MenC vaccine (primed between 2 months and 6 years of age). The response to a Haemophilus influenzae type b-MenC conjugate (Hib-MenC) booster was also measured. Methods: A phase 4 clinical trial was conducted among 250 healthy 6-12 year-old children. SBA titers were measured before, 1 month after, and 1 year after Hib-MenC administration. The correlate of protection was an SBA titer of ≥8. Results: An SBA titer of ≥8 was observed in 61 (25% [95% confidence interval CI, 20%-30%]) of 244 participants (mean age, 9.1 years; mean interval since MenC immunization, 6.75 years). The proportion with an SBA titer of ≥8 and the SBA geometric mean titer increased with age, from 12% (95% Ci, 4%-23%) to 48% (95% CI, 29%-67%) and from 2.90 (95% CI, 2.11-3.99) to 17.20 (95% CI, 6.80-43.5), respectively, from a mean age of 7.0 to 12.1 years. One month after the Hib-MenC booster, all participants had an SBA titer of ≥8, which was sustained in 99.6& at 1 year. Conclusions: As a result of waning antibody, the majority of 6-12 year-old children in the United Kingdom have inadequate serological protection against MenC. The persistence of MenC immunity and the response to a Hib-MenC booster is dependent on age at priming. A booster was highly effective in this cohort and could sustain population immunity against MenC disease.